Abdülhak Hamid ve Yahya Kemal'e Dair İki Mektup - Uçman, Abdullah (Kitabevi, 2003)
In this paper two letters about Abdülhak Hamid and Yahya Kemal are studied. One of the letters was written to Rıza Tevfik by Hüseyin Siret and the one was sent to Hüseyin Siret by Rıza Tevfik. Hüseyin Siret one of the most important literary portraits of their ages, member of Servet-i Fünun. Not only the text is considered. In addition the social circumstances of the period is olso told. These letters are firstly presented here.
Two Letters about Abdülhak Hamid and Yahya Kemal
Keywords: Abdülhak Hamid; Yahya Kemal; Servet-i Fünun; Hüseyin Siret; Turkish Literature